Intermittent hypoxia training does not change erythrocyte aggregation indicators in young, healthy men - Mardyła, Mateusz; Maciejczyk, Marcin; Pałka, Tomasz; Więcek, Magdalena; Kusmierczyk, Justyna; Szymura, Jadwiga; Szygula, Zbigniew (Frontiers in Physiology, 2024)
Background: The increasing popularity of hypoxic training as a training method to improve physical performance indicates the need to study the effects of this type of intervention on blood morphological and rheological indices, since the adaptive changes that follow such training mainly affect blood indices. In this study, the effects of a four weeks of intermittent hypoxic training on blood morphological and rheological indicators in physically active men were assessed. Methods: Forty-eight young, physically active men, participated in the study. Participants were randomly divided into three groups: two training groups and a control group without intervention (CTRL). Each group consisted of 16 participants. Training groups performed interval training (three times per week, 4 weeks, 12 workouts) under different conditions: in hypoxia (IHT; fraction of inspired oxygen (FiO2) = 14.4%) or in normoxia (NT; FiO2 = 20.9%). The control group performed only two workouts 4 weeks apart. Blood was taken during the first and last training session at rest, and three minutes after training. Results: After the last training session, there was a significant increase in mean corpuscular volume and a decrease in mean corpuscular haemoglobin concentration measured at rest only in the IHT group. There was also a significant decrease in resting aggregation amplitude for the IHT and CTRL groups. There was no difference in change of post-exercise plasma volume between first and last training session. Conclusion: The applied intermittent interval training in conditions of normoxia and hypoxia had no significant impact on resting aggregation parameters. This suggest that training under hypoxic conditions does not cause adverse rheological changes.